Identifying the uses of mobile technology among Library and Information Science undergraduate students. Issue 4 (6th September 2016) - Vassilakaki, Evgenia; Moniarou-Papaconstantinou, Valentini; Garoufallou, Emmanouel
Abstract : Purpose: Mobile technology has redefined the way people communicate and interact. In education, the number of academic institutions developing and offering mobile information services is growing steadily. The purpose of this paper is to identify the use of mobile technology by the Library Science and Information Systems undergraduate students in Greece. Design/methodology/approach: A questionnaire was developed drawing from the relevant literature and sent to undergraduate students studying Library and Information Science during the 2014-2015 academic year. Findings: It was found that students employed mobile phones for entertainment purposes whereas laptops and desktop computers for performing education-related tasks. Laptops and desktop computers were again mostly used to access library services, namely the OPAC, reference books, journals. Research limitations/implications: Academic institutions need to offer services and adopt online learning platforms supported in mobile devices. Students from other disciplines and their acceptance of mobile technology should be explored. Originality/value: This study identifies the specific mobile devices that students use to perform a variety of activities, educational and social, as well as the reasons for doing so.